Toll-Like Receptor 4 Signalling and Its Impact on Platelet Function, Thrombosis, and Haemostasis - Vallance, Thomas M.; Zeuner, Marie-Theres; Williams, Harry F.; Widera, Darius; Vaiyapuri, Sakthivel (Mediators of Inflammation, 2017)
Platelets are anucleated blood cells that participate in a wide range of physiological and pathological functions. Their major role is mediating haemostasis and thrombosis. In addition to these classic functions, platelets have emerged as important players in the innate immune system. In particular, they interact with leukocytes, secrete pro- and anti-inflammatory factors, and express a wide range of inflammatory receptors including Toll-like receptors (TLRs), for example, Toll-like receptor 4 (TLR4). TLR4, which is the most extensively studied TLR in nucleated cells, recognises lipopolysaccharides (LPS) that are compounds of the outer surface of Gram-negative bacteria. Unlike other TLRs, TLR4 is able to signal through both the MyD88-dependent and MyD88-independent signalling pathways. Notably, despite both pathways culminating in the activation of transcription factors, TLR4 has a prominent functional impact on platelet activity, haemostasis, and thrombosis. In this review, we summarise the current knowledge on TLR4 signalling in platelets, critically discuss its impact on platelet function, and highlight the open questions in this area.